Neurocommunication applied to increase tourist demand - Barrientos-Báez, Almudena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In the following article, the tourists who travel to Málaga and Vigo will be analysed, with the purpose of knowing the reason that has influenced the decision to opt for this cities before other national destinations, as well as to study the evolution of these cities in the area tourism, carry out a diagnosis of the leisure offer and see what decisions should be made in order to position itself as a permanent tourist resource over time. Through neuromarketing techniques such as sensory measurement, it is possible to verify in real time which tourist resource arouses positive emotional responses.